Miconia solearis, a new combination to replace the illegitimate Miconia magnifolia (Melastomataceae: Miconieae) in Tropical America - Gamba, Diana; Almeda, Frank (Phytotaxa, 2015)
In our recently published monograph of the Octopleura clade of Miconia Ruiz & Pavón (1794: 60, Gamba & Almeda 2014) we proposed a number of new combinations and new names to reflect the nested position of this assemblage of 33 species within the large and diverse Neotropical genus Miconia based on morphological and molecular data sets. In proposing the new name, Miconia magnifolia Gamba & Almeda (2014: 91), we overlooked the epithet of a heterotypic synonym that should have been adopted. Miconia magnifolia is therefore illegitimate and nomenclaturally superfluous according to Article 52.1 of the International Code of Nomenclature (McNeill et al. 2012) and is to be rejected because it included the type of a heterotypic synonym whose epithet was available and not already pre-empted in Miconia.